S. Dube (2017). Subjects of modernity. Time-space, disciplines, margins. Stellenbosch: Africa Sun Media. 180 pp. - Rufer, Mario (Estudios de Asia y África, 2020)
S. Dube (2017). Subjects of modernity. Time-space, disciplines, margins. Stellenbosch: Africa Sun Media. 180 pp.